2010
DOI: 10.1086/652402
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Untreated, UncomplicatedChlamydia trachomatisGenital Infection and Factors Associated with Chlamydia Resolution: A Review of Human Studies

Abstract: The majority of Chlamydia trachomatis genital infections in humans are asymptomatic and without clinical evidence of complications at the time of diagnosis. The natural history of chlamydial infection in humans, including the duration of infection and factors influencing resolution of infection, is not yet completely understood. This is in part attributable to the inherent challenges and ethical considerations in studying untreated chlamydia in humans. An improved understanding of the natural history of chlamy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
133
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(138 citation statements)
references
References 28 publications
4
133
1
Order By: Relevance
“…Most studies on spontaneous resolution of CT infection have reported the resolution frequency between the time of CT screening (typically with a nucleic acid amplification test [NAAT]) and returning for follow-up, usually for treatment of a positive test. Those with a positive CT screening test but negative CT test at follow-up are classified as having spontaneous resolution, which studies report occurs in 11% to 44% of individuals within a few weeks to several months of a positive screening CT NAAT [3]. We found a spontaneous resolution frequency of ~20% in subjects studied at a STD Clinic in Birmingham, AL [4].…”
Section: Persisting Genital Chlamydia Trachomatis (Ct) Infection Can mentioning
confidence: 54%
“…Most studies on spontaneous resolution of CT infection have reported the resolution frequency between the time of CT screening (typically with a nucleic acid amplification test [NAAT]) and returning for follow-up, usually for treatment of a positive test. Those with a positive CT screening test but negative CT test at follow-up are classified as having spontaneous resolution, which studies report occurs in 11% to 44% of individuals within a few weeks to several months of a positive screening CT NAAT [3]. We found a spontaneous resolution frequency of ~20% in subjects studied at a STD Clinic in Birmingham, AL [4].…”
Section: Persisting Genital Chlamydia Trachomatis (Ct) Infection Can mentioning
confidence: 54%
“…), which have been reported by others [15]. 10 Whether these indole-containing metabolites may be a source of indole or whether indole is present in the cervicovaginal environment in women remains to be elucidated.…”
mentioning
confidence: 70%
“…Natural clearance of Ct infection (i.e. resolving infection before treatment) occurs in 5 approximately 11-44% of women in the interval between a positive Ct screening test and returning for treatment [10]. Although the mechanisms involved in natural clearance are poorly understood, one study reported that women who naturally cleared Ct infection were 4-fold less likely to be re-infected within 6 months, suggesting adaptive immunity (perhaps via IFN--mediated tryptophan depletion) may contribute to natural clearance and protective immunity [11].…”
Section: Animal Models Of Chlamydia Infection Have Demonstrated That mentioning
confidence: 99%
“…In experimental animal models, in repeat infections, the enhanced inflammatory response may be mediated by cytotoxic CD8 + T cells primed against chlamydial heat shock protein 60 (cHSP60), producing greater tissue destruction and fibrosis than in the initial infection, this risk increasing with each additional reinfection (56,71). Serum and genital mucosal IgA and IgG antibodies to specific C. trachomatis proteins such as cHSP and to chlamydial elementary bodies (EBs) are usually detected during active infection in women (37), but their precise role in the resolution of infection remains unclear.…”
Section: Factors Involved In Etiopathogenesismentioning
confidence: 99%
“…Approximately half of infections resolve spontaneously in the first year after initial chlamydia testing, but in some women infections may persist for several years. The duration of infection and the chlamydial load in repeat infections seem to be lower than in the first infection, suggesting the existence of some degree of partial immunity (37). However, repeat infections are common and are associated with a higher risk of PID and sequels (41).…”
Section: Factors Involved In Etiopathogenesismentioning
confidence: 99%